Desenvolvimento de uniformes escolares - Fonseca, Isabela Santini (2014)
This project initially sought to identify with the method of observation and literature , what are the problems and modeling amounts that should be considered in the development of school uniforms for students 3-5 years. Focused primarily on the well-being and the resign of students. For the development of design concepts have been used , combining them with ergonomic modeling studies , for obtaining more uniform quality and comfort. In addition, the products were inserted elements such as pockets getting attractive for small users .